Taninos y fenoles en la fermentacion in vitro de leñosas forrajeras tropicales - Pinto Ruiz, R.=700 1 Hernandez Sanchez, D.
(ES, En)
Ilus., 32 ref.
Keywords: LEGUMINOSAS FORRAJERAS; TANINOS; POLIFENOLES; FACTORES ANTINUTRICIONALES; MEXICO; PRODUCCION DE GAS; AGRONOMIA MESOAMERICANA